Investigating the effect of wellbore perforation on sand production using hybrid numerical modeling in an Iranian oil field - Nemat Nemati; Kaveh Ahangari; Kamran Goshtasbi; Reza Shirinabadi; Morteza Azadpour (Scientific Reports)
Abstract Sand production is one of the phenomena that has adverse effects on the oil and gas industries yearly. One of the methods to control sand production, without the need to install mechanical equipment, is to design optimal perforating and directional perforating in the well. This study investigated this issue for the first time using a hybrid numerical modeling approach. For this purpose, a certain depth of a vertical well drilled in layer A10 of the Asmari reservoir located in one of the oil fields in southwestern Iran was modeled in two stages. In the first stage, eight wellbore models with different numbers of perforations (from one to ten) were constructed and run. Then, the values of cumulative sand production, sand production rate, and the intensity of drag force were measured for each mode. Four wellbore models were made, each perforated in different directions in the second stage. Then, the sand production rate in all four models was measured. The results obtained from the analysis showed that at a certain depth of the well, the more perforations there are, the higher the sand production rate. In other words, unlike some previous studies, increasing the number of perforations and consequently reducing the drag force will not affect reducing the sand production rate. In addition, in a vertical well under the normal stress regime, the highest sand production rate is related to the perforations created in the minimum horizontal stress direction, and the lowest value corresponds to the maximum horizontal stress direction.